2001
DOI: 10.1038/sj.onc.1204684
|View full text |Cite
|
Sign up to set email alerts
|

EWS-ATF-1 chimeric protein in soft tissue clear cell sarcoma associates with CREB-binding protein and interferes with p53-mediated trans-activation function

Abstract: The recurrent t(12;22) (q13;q12) chromosomal translocation associated with soft tissue clear cell sarcoma results in a chimeric protein EWS-ATF-1 that acts as a constitutive transcriptional activator. The CBP/p300 transcriptional coactivator, which links various transcriptional factors to basal transcription apparatus, participates in transcriptional activation, growth and cell cycle control and di erentiation. In this study, we show that EWS-ATF-1 associates constitutively with CBP both in vitro and in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…35 The EWS-ATF-1 36 whose mechanism of action appears to be targeted repression of the CBP/p300 transcriptional coactivator, resulting in loss of function of p53. 37 Although not diagnostically helpful, polysomy of chromosome 8 is another common cytogenetic abnormality in clear cell sarcoma. 11,31 Other molecular characteristics which may have diagnostic utility in the future include activating mutations in the BRAF gene, which have been demonstrated in a significant percentage of malignant melanoma, but not clear cell sarcoma, 38 and the protein product of the epidermal growth factor receptor ERBB3 gene, which has been reported to be a marker of clear cell sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…35 The EWS-ATF-1 36 whose mechanism of action appears to be targeted repression of the CBP/p300 transcriptional coactivator, resulting in loss of function of p53. 37 Although not diagnostically helpful, polysomy of chromosome 8 is another common cytogenetic abnormality in clear cell sarcoma. 11,31 Other molecular characteristics which may have diagnostic utility in the future include activating mutations in the BRAF gene, which have been demonstrated in a significant percentage of malignant melanoma, but not clear cell sarcoma, 38 and the protein product of the epidermal growth factor receptor ERBB3 gene, which has been reported to be a marker of clear cell sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…The EAD is known to contact a limited number of transcriptional components including the coactivator CBP (38,39), multiple TAFs (40), and the RNA polymerase II subunits rpb7 (40,41) and rpb5 (40). rpb7 and its partner rpb4 are required for EAD-mediated transactivation in yeast (42), suggesting that the EAD might flexibly wrap around rpb7/4 via multiple contacts, a mode of recognition that is used by known IDPs (7).…”
Section: Effect Of Ead Mutations On Transformation By Ews/fli1mentioning
confidence: 99%
“…CBP/p300 is shown to have a pivotal role in apoptotic pathway. Recently, we have found CBP to interact with EWS-ATF-1 and interfere with the transcriptional activity of p53, which requires CBP/p300 as a coactivator for transcriptional activation (Fujimura et al, 2001). These results have driven us to test whether EWS-Fli-1 or Fli-1 associates with CBP.…”
Section: Ews-fli-1 and Fli-1 Mutants That Are Deficient In Transcriptmentioning
confidence: 99%
“…It is proposed that E1A downregulates oncogene HER2/neu through the p300 pathway. We have demonstrated that EWS-ATF-1 in MMSP interacts with CBP and inhibits the transcriptional activity of target genes (Fujimura et al, 2001). EWS is also found to be associated with CBP/p300 (Rossow and Janknecht, 2001;Araya et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation